2006
DOI: 10.1016/j.enbuild.2006.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Occupant preferences and satisfaction with the luminous environment and control systems in daylit offices: a literature review

Abstract: /npsi/ctrl?lang=en http://nparc.cisti-icist.nrc-cnrc.gc.ca/npsi/ctrl?lang=fr Access and use of this website and the material on it are subject to the Terms and Conditions set forth at http://nparc.cisti-icist.nrc-cnrc.gc.ca/npsi/jsp/nparc_cp.jsp?lang=en NRC Publications Archive Archives des publications du CNRCThis publication could be one of several versions: author's original, accepted manuscript or the publisher's version. / La version de cette publication peut être l'une des suivantes : la version prépubli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
264
0
18

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 471 publications
(287 citation statements)
references
References 37 publications
5
264
0
18
Order By: Relevance
“…It is remarkable that, for most months in the year, the adaptable WWR values are larger than the static value. Larger WWR values indicate that in this case study CABS also increase the view to the outside, which is an important performance aspect in buildings [62]. As such, this finding shows a clear example of the promising role of CABS, together with the type of concessions [63] that is needed to design static building envelopes which are supposed to perform well under the wide range of different boundary conditions.…”
Section: <Figure 7>mentioning
confidence: 73%
“…It is remarkable that, for most months in the year, the adaptable WWR values are larger than the static value. Larger WWR values indicate that in this case study CABS also increase the view to the outside, which is an important performance aspect in buildings [62]. As such, this finding shows a clear example of the promising role of CABS, together with the type of concessions [63] that is needed to design static building envelopes which are supposed to perform well under the wide range of different boundary conditions.…”
Section: <Figure 7>mentioning
confidence: 73%
“…In fact as suggested by previous studies personal control over the work environment is necessary for individual well-being (Brager et al, 2004;Huang et al, 2004). Empirical studies also have indicated that the availability of choices in the physical environment will lead to better outcomes for employees, such as better performance and improved mood (Paciuk, 1990, Parker et al, 2013, Veitch and Gifford, 1996bGalasiu and Veitch, 2006). Based on the broaden-and-build theory of positive emotions, positive and good feelings change people's bodily systems and predict healthier mental and physical outcomes such as reducing stress and physical pain; it also modify people's perception and insight (Fredrickson, 2001;Fredrickson and Branigan, 2005).…”
Section: The Importance Of Individual Control Over the Physical Work mentioning
confidence: 91%
“…Nonetheless, the good indoor environmental quality can improve overall work, learning performance and reduce absenteeism. There are numbers of paper have recently reviewed, [10] point out on the effects of single environmental conditions on human such as examiné which conditions lead to satisfaction with the visual and acoustic environment .Besides that, studies by [11] concern about which factors are not significant to the indoor environment and again they highlighted more on satisfaction with a single environmental condition such as visual environment or thermal environment [12]. Subsequently, from the research studies tended to consider environmental comfort such as temperature, velocity, radiant temperature and humidity but none have considered lighting, noise and smell.…”
Section: Fig1 Examples Of How Climatementioning
confidence: 99%